Depression, anxiety and stress among dental undergraduate students: Prevalence, stressors and relieving factors - Yaacob, Munirah; Harun, Nor Asilah; Ramli, Farizah; Abdul Razak, Hannah; Sajuni, Noor Aisyah (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2018)
Aim: To investigate the depression, anxiety and stress, stressors and relieving factors among dental students at Kulliyyah of Dentistry (KOD). Materials and methods: A cross-sectional study was conducted among 222 dental students. Their socio-demographic data, self-reported depression, anxiety and stress (DASS-21) scores, causes and relieving factors were collected using validated semi-structured pre-tested questionnaires. The data was analysed using percentages, chi-square test and Binary logistic regression tests with SPSS version 24. Results: The prevalence of depression, anxiety and stress was 41%, 68.9% and 34.2% respectively. Cross analysis showed that academic-related and laboratory or clinical related reasons were significantly associated with the depressive symptoms [(X2= 15.86, p<0.0001) and (X2= 10.45, p=0.001) respectively] and stress symptoms [(X2= 19.95, p<0.0001) and (X2= 6.11, p<0.05) respectively] among dental student. Furthermore, the item ‘examination’ being the highest factor chosen in academic-related stressors. The response for stress-relieving factors was high for Islamic ritual prayer/spiritual activities (94.6%), sleeping (86.5%) and doing exercise/playing sports (76.1%), while ‘seeking professional help’ (19.8%) was the least. Conclusions: This study shows that depressive, anxiety and stress symptoms are prevalent among dental students. Islamic ritual prayer and involvement in spiritual related activities was found to be the most preferred way for students to relief stress. Hence, it is vital that the university continually evaluates the psychological health of the students, tailor preventive measures and spiritual related programs to help students to cope with stress.